Oxidative stress status in hypertensive patients on amlodipine treatment - Madhloom, Bahaa N; Diajil, Ameena R (Journal of Baghdad College of Dentistry, 2020)
Background: Oxidative stress may contribute to the etiology of hypertension in humans. Oxidative stress is an imbalance between reactive oxygen species (ROS) and antioxidant defense mechanisms, causing damage to biological macromolecules and dysregulation of normal metabolism and physiology. Amlodipine as an antihypertensive agent is a long-acting calcium channel blocker that dilates blood vessels and improves blood flow. The aim of this study was to assess the oxidative stress in hypertensive patients on Amlodipine treatment through the assessment of salivary Malondialdehyde (MDA) and superoxide dismutase (SOD) as a marker of oxidative stress. Material and method: 60 individuals were included in this study, divided into two groups; the first group composed of 30 hypertensive patients on Amlodipine antihypertensive agent. The second group, the control group, composed of 30 healthy subjects without any systemic disease and with almost healthy oral hygiene. Intraoral examination was done for each individual and salivary samples were collected with the salivary flow rate (F/R) which was calculated in ml per minute and pH was measured by pH meter. Salivary MDA and SOD were analyzed by using ELISA kit based on the principle of competitive enzyme immunoassay technique; the concentrations of markers were measured by spectrophotometer at 450nm in a microplate reader. Results: Salivary MDA was significantly higher in hypertensive patients compared to control, while salivary SOD was significantly lower in patients than control group. Salivary flow rate and pH was significantly lower in patients as compared to the control group. Conclusions: There is a relation between oxidative stress and hypertension. Salivary MDA and SOD can be used as potential marker for monitoring patients with Hypertension. Keywords: hypertension, Oxidative stress, Amlodipine, MDA and SOD